2011
DOI: 10.1136/ard.2011.150250
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of the 2009 non-adjuvanted influenza A/H1N1 vaccine in a large cohort of autoimmune rheumatic diseases

Abstract: The novel recognition of a diverse vaccine immunogenicity profile in distinct ARDs supports the notion that a booster dose may be recommended for diseases with suboptimal immune responses. This large study also settles the issue of vaccine safety. (ClinicalTrials.gov #NCT01151644).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 37 publications
9
70
3
2
Order By: Relevance
“…Patients with JDM had a deficient seroconversion rate, which is in accord with a report for the same vaccine in adult DM 21 . This finding may be associated with the underlying pathology of this disease, which is known to involve the humoral endotheliopathy initiated by complement deposition in intramuscular blood vessels 28 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Patients with JDM had a deficient seroconversion rate, which is in accord with a report for the same vaccine in adult DM 21 . This finding may be associated with the underlying pathology of this disease, which is known to involve the humoral endotheliopathy initiated by complement deposition in intramuscular blood vessels 28 .…”
Section: Discussionsupporting
confidence: 73%
“…The lower immune response to vaccine that we observed in the primary vasculitis group contrasts with the adequate response in reports concerning adult patients with granulomatosis with polyangiitis immunized with seasonal 29 and pandemic H1N1 vaccine 21 . The most likely explanation for this discrepancy is the limited number of children with primary vasculitis analyzed in our study and the underrepresentation of granulomatosis with polyangiitis in our sample.…”
Section: Discussioncontrasting
confidence: 54%
“…Among other immunocompromised populations, primarily cancer patients and transplant recipients (individuals receiving hematopoietic stem cell or solid organ transplants), single doses of both unadjuvanted and adjuvanted inactivated influenza vaccines have solicited only moderate immunological responses in adults [269,[273][274][275][276][277][278][279] and children. [280][281][282] Many of these studies found that a second dose significantly improved the proportion achieving serological protection.…”
Section: Disease Burdenmentioning
confidence: 99%
“…Further studies should now address whether some vaccines may induce a relapse or worsen the course of the disease in patients previously diagnosed with ITP, as has already been investigated for rheumatoid arthritis and systemic lupus erythematosus. [34][35][36][37] …”
Section: Org Frommentioning
confidence: 99%